Aktivitas Antihiperlipidemia Ekstrak Etanol Daun Annona squamosa L. - Rofida, Siti; Firdiansyah, Ahmad; Fitriyastuti, Endah (Jurnal Farmasi Sains dan Terapan, 2015)
Cause of cardiovascular disease risk factors, one of which is a high cholesterol levels in serum. Mortality caused by cardiovascular disease as 17.3 million people. Annona squamosa L. or commonly referred custard apple is a plant from family Annonaceae and have been used for insecticide, antitumor, antidiabetic, antioxidant, anti-inflammatory, and antihyperlipidemia. The leaves of Annona squamosa L. contains acetogenin, diterpene, flavonoids, lignin, hydroxyl ketones, and benzoquinazolin. The aims of this study is to determine the optimum dose to reduce levels of LDL on hyperlipidemic rats. In this study, hyperlipidemic rats were divided into 5 groups, negative control group (normal feed), positive control group (normal feed and simvastatin at a dose of 0.9 mg/KgBW), treatment group 1 (normal feed and ethanol extract leaves of Annona squamosa L. at a dose of 0.25 mg/gBB, treatment groups 2 (normal feed and ethanol extract leaf of Annona squamosa L. at a dose of 0.75 mg/gBB, treatment groups 3 (normal feed and ethanol extract leaf of Annona squamosa L. at a dose of 1 mg/gBB). The results of identification by thin-layer chromatography on ethanol extract leaf of Annona squamosa L indicates the presence of flavonoids. The results showed that the ethanol extract leaves of Annona squamosa Linn. On hyperlipidemia rats, can lower LDL cholesterol levels at doses of 0.25 mg/gram BB.